2011
DOI: 10.1590/s0102-311x2011000200003
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, health-related quality of life and depression during pregnancy

Abstract: This study examines physical activity patterns among women, from pre-pregnancy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
1
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 49 publications
9
52
1
12
Order By: Relevance
“…As mentioned above, it is possible that the majority of time spent on physical activity reported by this sample consists of housework and manual occupational activities. Time spent on work-related activities throughout pregnancy remained stable in comparison to the pre-pregnancy pattern 9 . The practice of leisure-time physical activity, which is more likely to decrease during pregnancy 7,9 , is more common in populations with higher levels of education and socioeconomic status 6 .…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…As mentioned above, it is possible that the majority of time spent on physical activity reported by this sample consists of housework and manual occupational activities. Time spent on work-related activities throughout pregnancy remained stable in comparison to the pre-pregnancy pattern 9 . The practice of leisure-time physical activity, which is more likely to decrease during pregnancy 7,9 , is more common in populations with higher levels of education and socioeconomic status 6 .…”
Section: Discussionmentioning
confidence: 87%
“…Two previous studies that used similar instruments to measure physical activity (long version of the IPAQ) among women in the same gestational trimester reported rates of 64.5% 9 and 87.5% 8 . It must be emphasized, however, that these studies used different cutoff points (at least 150 minutes of physical activity per week) 8,9 . A populationbased study carried out by Evenson et al 6 using an instrument that classified level of physical activity based on metabolic equivalents, reported that 84.2% of pregnant women were physically inactive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations